2018
DOI: 10.1007/s40089-018-0254-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the feasibility of development of nanomaterial-based microwave absorbers

Abstract: Advancement in the use of microwave electronics by the wireless devices, networks' server and switches, wireless antenna systems, and mobile phone base station potentially increased the radio-frequency interference. Effective elimination of this electromagnetic pollution is very necessary for proper working of electronic equipments. Microwave absorbers serve the above purpose leading to have enormous commercial and defence applications, for antenna shielding and laboratory testing of antenna. Researchers are, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Serious electromagnetic interference (EMI) has attracted massive attention nowadays. Tremendous efforts have been paid to designing and fabricating advanced microwave absorption (MA) materials featured by thin thickness, light weight, strong absorption, and a wide effective bandwidth. Among MA materials reported previously, core–shell nanocomposites are highly expected to be promising candidates due to their small sizes, large surface areas, and unique microstructures and electromagnetic properties. To date, many core–shell nanocomposites have been developed, including carbon (C)-coated Fe, Co, , Ni, and their alloys, or oxide-based nanostructures. , The intriguing MA performances of these nanocomposites motivate strong expectations on understanding the MA mechanisms of nanocomposite absorbers. , For example, Wang et al found that the MA performance of Ni–C core–shell nanoparticles (NPs) could be tuned by the thickness of C shells . Kuang et al investigated the effects of metal cores and C shells on the MA performance of FeCo–C and FeNi–C core–shell nanoparticles by experimental results and equivalent circuit models and found that the morphology of C shells and magnetic alloyed cores have significant influences on their MA performances. , However, for the above-mentioned magnetic core–shell nanoparticles, the small size effects, complicated core–shell interface effects, and potential synergy effects with the magnetic loss of the nanocores may affect the measured MA properties.…”
Section: Introductionmentioning
confidence: 99%
“…Serious electromagnetic interference (EMI) has attracted massive attention nowadays. Tremendous efforts have been paid to designing and fabricating advanced microwave absorption (MA) materials featured by thin thickness, light weight, strong absorption, and a wide effective bandwidth. Among MA materials reported previously, core–shell nanocomposites are highly expected to be promising candidates due to their small sizes, large surface areas, and unique microstructures and electromagnetic properties. To date, many core–shell nanocomposites have been developed, including carbon (C)-coated Fe, Co, , Ni, and their alloys, or oxide-based nanostructures. , The intriguing MA performances of these nanocomposites motivate strong expectations on understanding the MA mechanisms of nanocomposite absorbers. , For example, Wang et al found that the MA performance of Ni–C core–shell nanoparticles (NPs) could be tuned by the thickness of C shells . Kuang et al investigated the effects of metal cores and C shells on the MA performance of FeCo–C and FeNi–C core–shell nanoparticles by experimental results and equivalent circuit models and found that the morphology of C shells and magnetic alloyed cores have significant influences on their MA performances. , However, for the above-mentioned magnetic core–shell nanoparticles, the small size effects, complicated core–shell interface effects, and potential synergy effects with the magnetic loss of the nanocores may affect the measured MA properties.…”
Section: Introductionmentioning
confidence: 99%